2014
DOI: 10.1063/1.4895095
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Supramolecular structures in monohydroxy alcohols: Insights from shear-mechanical studies of a systematic series of octanol structural isomers

Abstract: Communication: Slow supramolecular mode in amine and thiol derivatives of 2-ethyl-1-hexanol revealed by combined dielectric and shear-mechanical studies

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
43
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 35 publications
4
43
1
Order By: Relevance
“…This is at odds with the common observation where decrease in the intensity of the dielectric Debye relaxation is followed by a decreased separation between the alpha and the Debye relaxation (e.g., Ref. 25). The invariant time scale separation could suggest that the size of the supramolecular structures is comparable in the three systems, but this is very speculative.…”
contrasting
confidence: 53%
See 3 more Smart Citations
“…This is at odds with the common observation where decrease in the intensity of the dielectric Debye relaxation is followed by a decreased separation between the alpha and the Debye relaxation (e.g., Ref. 25). The invariant time scale separation could suggest that the size of the supramolecular structures is comparable in the three systems, but this is very speculative.…”
contrasting
confidence: 53%
“…49 A crossover from an intermediate to the terminal power law reported for shortchain polymers, polymeric liquids, or monoalcohols (ν 0.7 ) is an evidence of an additional slow supramolecular organization/dynamics. [23][24][25]42,50 In the present study, due to resolution limits of the PSG technique, we were not able to clearly observe the change of the frequency dependence of G ′ and G ′′ at modulus values lower than 1 MPa. However, the power law of the lowfrequency part of the mechanical loss shear spectra for amine (ν 0.85 ) and thiol (ν 0.93 ) shows that they display an intermediate behavior between the one reported for non-associating and associating liquids.…”
mentioning
confidence: 38%
See 2 more Smart Citations
“…For long time the observation of the Debye-like process by other techniques than dielectric spectroscopy remained elusive, but slow dynamics additional to that of the structural relaxation have already been reported by a number of techniques [10][11][12][13][14][15] and most revealingly by shear modulus measurements [16][17][18]. Moreover, very recently and aided by complex viscosity η * (ω) representation of shear data, authors have reported for the first time the presence of an additional process, intermediate between those previously indentified [19].…”
mentioning
confidence: 98%